Innovative Hostel Interiors for User Satisfaction - Sania Ehsan; Deepti Pande Rana; Arun Kapur (International Journal of Environmental Planning and Development Architecture, 2024)
This research paper delves into innovative design strategies for hostel interiors with a focus on enhancing user satisfaction. It investigates key elements such as space optimization, comfort, functionality, and technological integration, while also considering sustainability. The study reviews contemporary design trends and challenges in hostile environments, highlighting successful approaches through detailed case studies. By analyzing how these design strategies impact user experience, the research underscores the significance of creating functional, aesthetically pleasing, and user-centric spaces. The findings reveal that integrating smart technologies, optimizing communal areas, and adopting sustainable practices can substantially improve resident satisfaction. The paper concludes with practical recommendations for future hostel designs and explores emerging trends poised to shape the future of hostel interiors
Keywords: Hostel design; comfort and functionality; interior design innovation; smart technologies; space optimization; sustainable design; user satisfaction